CULTURAL AND CRITICAL PEDAGOGY REVISITED: A CASE OF TEACHER’S AGENCY IN A CLASS WITH CLASH OF VALUES - Panji Agnyoto (Fakultas Ilmu Budaya and LPPM Universitas Sebelas April, 2022)
In some non-English speaking countries, English dominance has, at least since globalization aroused, been a hot debated issue, not merely due to its cultural contents and its ideology to diminish the influence of native languages and their embedded cultures but also its dilemmas which have been striking many students and educators. From the intercultural perspective, English mastery necessitates English cultural contents as cultural competence to achieve, but critically speaking, promoting target culture is a hidden agenda to westernize the people. This study aims to investigate how those two paradigms are at play in English instructions, and how the teacher deals with target and local culture contents. This study is conducted in a micro-ethnography approach. It employs document analyses, classroom observation and teacher-students interactions, and an interview with the teacher to collect the data at one Islamic International School in Batu. The result shows that both target and local cultural contents are conflicted as a consequence of international curriculum and Islamic identity of the school. However, there is also teacher’s thrusting personal agenda to mediate both contents and her own culture preoccupation which can be seen from the organization of classroom activities, teacher’s feedback, and teacher’s conclusion. It is suggested that future research combine both micro and macro levels of analyses from students’ and teacher’s cultural background and from the classroom activities to schooling process. From the explication of the findings and discussion it is also recommended that the teacher be cautious in selecting teaching materials so as not to evoke culture bias.